E LEARNING:PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI INFORMASI - Setyoningsih Setyoningsih (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
The rapid development in information technology in this era of globalization enables the development of better information services in the field of education. One of the new innovations in the use of instructional media and technology-based learning resources and information is e-Learning. The term e-Learning contains a very broad sense so that many experts elaborate on the definition of e-Leaning from various viewpoints. E-learning or electronic learning is learning that utilizes the internet in learning activities by making the electronic facilities as a learning medium. The concept of e-Learning has had an impact in the transformation process of conventional education into digital form, both contents and the system. In addition, the internet media make the interaction between faculty and students both in the form of real time or not.